Breakdown Characteristics of Oil-Pressboard Insulation under AC-DC Combined Voltage and Its Mathematical Model - Qingguo Chen; Jinfeng Zhang; Minghe Chi; Chong Guo (Energies, 2018)
An AC-DC combined voltage is applied to the oil-pressboard insulation near the valve side during the operation of a converter transformer. To study the breakdown characteristics of an oil-pressboard insulation under such voltages, a typical plate electrode structure was employed in the laboratory to conduct a breakdown test on the oil-pressboard insulation. The electrical field distribution and the DC contents of the transformer oil and the pressboard in composite insulation under the AC-DC combined voltage were simulated by their dielectric parameters. The breakdown strength of the transformer oil decreases with the increase in the DC content of the applied voltage, whereas that of the pressboard increases. For the oil-pressboard insulation, the breakdown voltage increases first and then decreases. The electric field strength decreases in the transformer oil with the increase in the DC content, whereas it increases in the pressboard. And the DC contents of the transformer and the pressboard in composite insulation were different from that of the applied voltage. Finally, based on the above results, a mathematical model was proposed to describe the breakdown characteristics of the oil-pressboard insulation under the AC-DC combined voltage; the theoretical and experimental results were in good agreement.